(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The world of Anita Desai’snovels is an ambivalent one; it is a world where harmony is aspired but oftennot achieved; and the desire to live life fully with proper zeal and love,clashes, at times violently, with the desire to withdraw and keep inwards.Instinct, emotion, passion appear to be strangers in the world of sordid dailyroutine. Anita Desai’s fictions are marked by ‘existential’ themes. Aspects of‘existentialism’ are reflected in her characters in the form of fragmentedindividuals, alienated and estranged, both emotionally and spiritually, fromthe ‘normal society’.